Frequency Reconfigurable Monopole Antenna for Multimode Wireless Communications - Ojaroudi, Nasser; Ghadimi, Noradin; Ojaroudi, Yasser; Ojaroudi, Sajjad (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper describes a compact reconfigurable microstrip antenna for multimode wireless communications, whose frequency characteristic can be reconfigured electronically to operate at 2.4 GHz (Bluetooth), 3.5 GHz (WiMAX) or 5.2/5.8 GHz (WLAN). The presented microstrip monopole antenna consists of an open-stub microstrip line with two inverted coupled U-shaped parasitic structures and ground plane. Reconfigurability is obtained by implementing two PIN diodes across the antenna structure and biasing these active elements. The proposed antenna can obtain good return loss property with -38 dB at 2.4 GHz, -42 dB at 3.5 GHz and -47 dB at 5.5 GHz. The proposed microstrip antenna fabricated on an FR4 substrate with thickness of 1.6 mm, relative permittivity of 4.4 and has a small size of 12×18 mm2 . The measured return loss characteristics are in good agreement with simulated results, which verified the reliability of the designed antenna. So this new design should have many applications in the circuit where reconfigurable antenna is used.